Lightning Surge Analysis On A Large Scale Grid-connected Solar Photovoltaic System - Nur Hazirah Zaini; Mohd Zainal Abidin Ab. Kadir; Mohd Amran Mohd Radzi; Mahdi Izadi; Norhafiz Azis; Nor Izzati Ahmad; Mohd Solehin Mohd Nasir (MDPI Energies, 2024)
Indexed by SCOPUS